Kepemimpinan Kepala Sekolah dalam Meningkatkan Profesionalisme Guru di SMP Negeri 40 Purworejo - Siti Zulaikah (LPPM IAINU Kebumen, 2020)
This research is based on the leadership of the principal who is quite good. In this regard, this study aims to determine the leadership of the principal in increasing teacher professionalism at SMP Negeri 40 Purworejo. This study uses qualitative research that focuses on natural phenomena and is analyzed using logical scientific thinking. As for the technique of data collection in this research, it was obtained through observation, interviews, documentation, and triangulation. Data analysis was carried out by data reduction, data presentation, and data verification then formulating conclusions on the results of the research conducted. There are three things put forward in this study, namely: (1) the managerial ability of the principal in relation to the chief officer in increasing the professionalism of teachers at SMP Negeri 40 Purworejo has been proven to produce vision and mission products for schools that have been implemented properly although not all of them, and to achieve it needed good cooperation with all elements of the school; the role of the school principal to create a harmonious atmosphere in the school environment, by giving teachers assignments according to their main duties and teachers can carry out their duties and responsibilities professionally; provide opportunities for educators to improve their profession; (2) the ability of the school principal's sense of business to improve teacher professionalism, as evidenced by the ability of the school principal to manage education funds, especially in finding sources of education funds to meet the needs of education; (3) the ability of the school principal's sense of education in increasing teacher professionalism, which is proven by the ability of the school principal to carry out mental development, moral development, physical development and artistic development which is carried out in a programmed manner.